2013
DOI: 10.1242/dev.095810
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of delta-like 1 homolog (DLK1) in skeletal muscle development and adult muscle regeneration

Abstract: SUMMARYMuscle development and regeneration is tightly orchestrated by a specific set of myogenic transcription factors. However, factors that regulate these essential myogenic inducers remain poorly described. Here, we show that delta-like 1 homolog (Dlk1), an imprinted gene best known for its ability to inhibit adipogenesis, is a crucial regulator of the myogenic program in skeletal muscle. Dlk1 −/− mice were developmentally retarded in their muscle mass and function owing to inhibition of the myogenic progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
77
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 37 publications
7
77
1
Order By: Relevance
“…Such effects are expected because during development, power over phenotypes is commonly (i) some function of time, because events earlier in ontogeny have larger, more-cascading effects, and (ii) some function of control over rates and patterns of cell and tissue proliferation, because this is how organisms grow and differentiate. This prediction is well supported by recent studies showing that in a wide range of human tissues, imprinted genes orchestrate stem cell replication versus inhibition [96][97][98], and by the observation that imprinted genes exert especially pervasive effects on placental development, at the start of fetal growth and development [99,100]. Imprintedgene conflicts will therefore be especially important in mediating causes of variation in physical health, because so many human health outcomes are highly dependent on early-life events and phenotypes such as placental function and birth weight [101], and on the roles of stem cells in tissue renewal and repair.…”
Section: (D) Intragenomic Conflicts Mediate Disease Risks and Phenotypessupporting
confidence: 54%
“…Such effects are expected because during development, power over phenotypes is commonly (i) some function of time, because events earlier in ontogeny have larger, more-cascading effects, and (ii) some function of control over rates and patterns of cell and tissue proliferation, because this is how organisms grow and differentiate. This prediction is well supported by recent studies showing that in a wide range of human tissues, imprinted genes orchestrate stem cell replication versus inhibition [96][97][98], and by the observation that imprinted genes exert especially pervasive effects on placental development, at the start of fetal growth and development [99,100]. Imprintedgene conflicts will therefore be especially important in mediating causes of variation in physical health, because so many human health outcomes are highly dependent on early-life events and phenotypes such as placental function and birth weight [101], and on the roles of stem cells in tissue renewal and repair.…”
Section: (D) Intragenomic Conflicts Mediate Disease Risks and Phenotypessupporting
confidence: 54%
“…It is also called Pref-1, a factor involved in adipogenesis (20,21,50). Some previous studies had implicated DLK1 and its homologs as positive regulators in LIN-12/ NOTCH signaling (25,51,52), whereas other studies had shown the opposite or no effect of DLK1 on NOTCH signaling (26,27,50,(53)(54)(55)(56). These seemingly contradictory results could be due to different experimental systems used in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…The membrane-bound form of DLK1 can also be cleaved to generate soluble peptides (58). These different isoforms of DLK1 proteins could exhibit opposite effects in cell signaling and development (45,55,60,61). Therefore, DLK1 may act as a positive or negative regulator of NOTCH signaling under different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…If the point mutation occurs in both the paternal and maternal alleles, it causes no change in DLK1 protein expression (4), which is consistent with the mode of inheritance of the CLPG phenotype. It has been demonstrated that DLK1 protein expression is essential for determining muscle mass (20)(21)(22)(23)(24). Thus, a hypothesis predicting that maternal noncoding RNA might act as a negative regulator of DLK1 expression has been put forth; however, this hypothesis lacks evidence (25).…”
mentioning
confidence: 99%